Responsabilidade social e abertura de capitais: uma descrição dentro do complexo agroindustrial canavieiro do Brasil - Novaes, Elisa Nogueira (2009)
The companies of the sugar-alcohol sector kept the same characteristics since their beginning up to the nineties. They were controlled by oligarchic groups, were under the State protection and were not worried about dissociating from the negative stigma of exploiting the workforce and destroying the environment. In the beginning of the XXI century, the sector started two new movements that would change its profile: the opening of capital of some plants and the interest in actions related to Social Responsibility. The proposal of this dissertation is to investigate which were the main factors that contributed to the beginning of these initiatives and whether there is any relationship between the opening of capital, and the adoption of actions related to Social Responsibility in the Agroindustrial Complex Sugar from Brazil. Within this context, it was possible to find out that the main transformations were initiated in the nineties. The end of the indirect support from the State; the impoverishment of resources received by the producers in São Paulo; and the withdrawal of the State from the market regulations forced the entrepreneurs to establish in the market based on their own competence. Nowadays, the good perspectives of marked for the Complex have contributed to the introduction of new ways of organizing corporative strategies in the companies of this sector. Social Responsibility that was not taken into account before became an important issue. Some important facts revealed during this research raise some questions about the relationship between Social Responsibility and the opening of capital, giving place to a new investigation that can be a subject for another research.